Deep roots for mid-ocean-ridge volcanoes revealed by plagioclase-hosted melt inclusions - Bennett, Emma; Jenner, Frances; Millet, Marc-Alban; Cashman, K V; Lissenberg, C J (Nature, 2019)
The global mid-ocean ridge system is the most extensive magmatic system on our planet and is the site of 75 per cent of Earth’s volcanism. The vertical extent of mid-ocean-ridge magmatic systems has been considered to be restricted: even at the ultraslow- spreading Gakkel mid-ocean ridge under the Arctic Ocean, where the lithosphere is thickest, crystallization depths of magmas that feed eruptions are thought to be less than nine kilometres. These depths were determined using the volatile-element contents of melt inclusions, which are small volumes of magma that become trapped within crystallizing minerals. In studies of basaltic magmatic systems, olivine is the mineral of choice for this approach. However, pressures derived from olivine-hosted melt inclusions are at odds with pressures derived from basalt major-element barometers and geophysical measurements of lithospheric thickness. Here we present a comparative study of olivine- and plagioclase-hosted melt inclusions from the Gakkel mid-ocean ridge. We show that the volatile contents of plagioclase-hosted melt inclusions correspond to much higher crystallization pressures (with a mean value of 270 megapascals) than olivine-hosted melt inclusions (with a mean value of 145 megapascals). The highest recorded pressure that we find equates to a depth 16.4 kilometres below the seafloor. Such higher depths are consistent with both the thickness of the Gakkel mid-ocean ridge lithosphere and with pressures reconstructed from glass compositions. In contrast to previous studies using olivine-hosted melt inclusions, our results demonstrate that mid-ocean-ridge volcanoes may have magmatic roots deep in the lithospheric mantle, at least at ultraslow-spreading ridges.